Indonesia Pengaruh Kepemimpinan, Lingkungan kerja, dan Etika kerja islami terhadap Kepuasan kerja Islam - Bagas Bambang Pamujo; Yayan Firmansyah (JEM Jurnal Ekonomi dan Manajemen, 2021)
Increasing global competition shows that every organization is required to improve the quality of work of members of the organization including their job satisfaction. However, so far, little research has been done on employee Islamic job satisfaction. This study aims to analyze employee Islamic job satisfaction and the factors that influence it, namely leadership, work environment, and Islamic work ethic. The method used in this research is quantitative. The research was conducted by involving 75 respondents. The results of the analysis show that transformational leadership, work environment, and Islamic work ethic have a significant effect on Islamic job satisfaction, while transactional leadership has no significant effect on Islamic job satisfaction.